Dynamic scoring of tax reforms in the European Union - Salvador Barrios; Mathias Dolls; Anamaria Maftei; Andreas Peichl; Sara Riscado; Janos Varga; Christian Wittneben (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
In this paper, we present the first dynamic scoring exercise linking a microsimulation and a dynamic general equilibrium model for Europe. We illustrate our novel methodology analysing hypothetical reforms of the social insurance contributions system in Belgium. Our approach takes into account the feedback effects resulting from adjustments and behavioral responses in the labor market and the economy-wide reaction to the tax policy changes, essential for a comprehensive evaluation of the reforms. We find that the self-financing effect of a reduction in employers' social insurance contribution is substantially larger than that of a comparable reduction in employees' social insurance contributions.
Keywords: H20; 330; Tax Reform; European Union.